Synthesis, characterization and in vitro anticancer activity of thiabendazole-derived 1, 2, 3-triazole derivatives. (7th July 2020) - El Bourakadi, Khadija; Mekhzoum, Mohamed El Mehdi; Saby, Charles; Morjani, Hamid; Chakchak, Hind; Merghoub, Nawal; Qaiss, Abou el kacem; Bouhfid, Rachid
Abstract : Thiabendazolium salts with 1, 2, 3-triazole motifs were synthesized and characterized; they exhibit good cytotoxic activity. Abstract : A series of thiabendazole-derived 1, 2, 3-triazole compounds were synthesized in good yields via 1, 3-dipolar cycloaddition through click chemistry approach using different chain alkyl azides with 4-(1-(prop-2-yn-1-yl)benzimidazole-2-yl)thiazole in the presence of copper(i ) catalyst. These compounds were characterized on the basis of FT-IR, 1 H NMR, 13 C NMR as well as mass spectrometry. The newly synthesized compounds were screened for their in vitro antiproliferative activity against a panel of three human cancer cell lines (HT29, MDA-MB-231 and SKBR3). Compound 4g exhibited significant activity against all the cell lines tested, with IC50 values ranging from 1.28 and 7.72 μg mL −1, inducing caspases 3 and 7, which further confirms the contribution of apoptotic cell death in MCF-7 and MDA-MB-231 cells. This work further demonstrates the anticancer properties of 4g, inducing apoptotic cell death, and the structure activity association is also discussed. This product could be a promising chemotherapeutic agent for cancer treatment.